2013
DOI: 10.1186/1471-213x-13-40
|View full text |Cite
|
Sign up to set email alerts
|

The Krüppel-like factor 2 and Krüppel-like factor 4 genes interact to maintain endothelial integrity in mouse embryonic vasculogenesis

Abstract: BackgroundKrüppel-like Factor 2 (KLF2) plays an important role in vessel maturation during embryonic development. In adult mice, KLF2 regulates expression of the tight junction protein occludin, which may allow KLF2 to maintain vascular integrity. Adult tamoxifen-inducible Krüppel-like Factor 4 (KLF4) knockout mice have thickened arterial intima following vascular injury. The role of KLF4, and the possible overlapping functions of KLF2 and KLF4, in the developing vasculature are not well-studied.ResultsEndothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 35 publications
2
55
0
Order By: Relevance
“…In parallel to this, our findings from in vitro ATAC-seq revealed that Nos3 open chromatin regions (R1-R3) also contain binding sites for KLFs, SP1, and the ETS-family of TFs, which can regulate Nos3's expression through another feedback mechanism under HG stress (Supplemental Tables 5-7). This observation is supplemented by the fact that Klf2 and Klf4 ablation in embryos resulted in EC disruption by reducing Nos3 expression (60). Further characterization of these TFs on Nos3 enhancer regulation upon HG exposure is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel to this, our findings from in vitro ATAC-seq revealed that Nos3 open chromatin regions (R1-R3) also contain binding sites for KLFs, SP1, and the ETS-family of TFs, which can regulate Nos3's expression through another feedback mechanism under HG stress (Supplemental Tables 5-7). This observation is supplemented by the fact that Klf2 and Klf4 ablation in embryos resulted in EC disruption by reducing Nos3 expression (60). Further characterization of these TFs on Nos3 enhancer regulation upon HG exposure is needed.…”
Section: Discussionmentioning
confidence: 99%
“…We also note that our findings are consistent with but add significantly to previous findings. Specifically, Chiplunkar et al (13) reported the role of both factors in regulating vascular integrity using systemic knockout embryos of both Klf2 and Klf4 genes. However, their study used a global deletion of Klf2 and Klf4 genes in the embryos and focused on early development.…”
Section: Discussionmentioning
confidence: 99%
“…It was further shown that the lack of Klf4 in these mice decreased the expression of many cardiac genes, including myosin light polypeptide 1 (Myl1), cardiac/slow skeletal troponin C (Tnnc1), myosin binding protein C (Mybpc2), natriuretic peptide precursor type B (Nppb) and Gata4 (Yoshida et al, 2010). An independent study showed that Klf2/Klf4 double knockout mice die earlier than the single knockouts, possibly due to gross hemorrhaging of multiple vessels (Chiplunkar et al, 2013a). Thus, KLF4 might play a role in vasculogenesis and the maintenance of embryonic vascular integrity by interacting with KLF2.…”
Section: Cardiovascular Developmentmentioning
confidence: 99%